Transgressive Spatiality and Multiple Temporality in Jim Crace’s Arcadia - Chalupský, Petr (American & British Studies Annual, 2022)
Arcadia (1992), Jim Crace’s most distinctively urban novel, bears the idiosyncratic features of its author’s writing: it is a deceptively simple story of vague geographical and historical setting conceived as a parable of the current world concerns, it portrays a community in a transitional moment of its existence, and it places special emphasis on spatial representations of its fictitious environment which assume metaphorical properties that convey the story’s rich ideas. Moreover, as a writer focusing on moral issues with a leftist political outlook, Crace has been consistent in his criticism of the neoliberal market economy and its negative impacts on communal values, a view which is also voiced in the novel. This paper makes use of the theoretical premises of Transmodernism as well as analytical tools of phenomenologically focused geocriticism to demonstrate that Arcadia can be subsumed within so-called transmodern fiction. This critique of globalized capitalism is carried out through sites Eric Prieto terms as the entre-deux, the in-between. Accordingly, the paper attempts to demonstrate how the novel’s liminal and heterogeneous places display non-linear and complexly interrelated temporalities which are indicative of their role within the city’s progress.